The Impact of Management, Family and Employee Ownership Concentration on Firm Performance - Michael Amroudi (Junior Management Science (JUMS), 2021)
This thesis investigates the relation between ownership structure and firm performance using a sample of 2,120 publicly traded European companies. The question of whether this relation should be positive or negative has been the subject of a wide-ranging discussion and was addressed by many researchers. Of particular interest have been management, family, and employee owners. Nevertheless, there is no consensus in the literature, and empirical studies on European companies are scarce. Utilising data from the European Federation of Employee Share Ownership (EFES) and the Bureau Van Dijk Orbis database, this relation is analysed using multiple linear regression with continuous and categorical predictors. The results show that firms having a management owner concentration up to strategic levels report a significantly higher Tobin's Q than firms having a no or no significant management concentration. The same effect holds true for family owners and employee owners. Measuring the ownership structure as the fraction of shares of the largest shareholder does not yield a significant effect and highlights the value of management, family, and employee owners.
Keywords: 650; Ownership concentration; family ownership; management ownership; employee ownership; firm performance